2019
DOI: 10.1021/acs.jafc.9b04860
|View full text |Cite
|
Sign up to set email alerts
|

Potential Correlation between Dietary Fiber-Suppressed Microbial Conversion of Choline to Trimethylamine and Formation of Methylglyoxal

Abstract: Dietary interventions alter the formation of the disease-associated metabolite, trimethylamine (TMA), via intestinal microbial TMA lyase activity. Nevertheless, the mechanisms regulating microbial enzyme production are still unclear. Sequencing of the gut bacteria 16S rDNA demonstrated that dietary intervention changed the composition of the gut microbiota and the functional metagenome involved in the choline utilization pathway. Characterization of the functional profile of the metagenomes and metabonomics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Consistent with this, a recent study investigated concentrations of fecal and serum BAs in vegans and omnivores, showing a vegan diet low in fat and high in fiber was positively correlated with fecal BA concentrations (118). Additionally, Li et al have suggested that supplying the DF diet to mice can reduce TMA and TMAO outputs via inhibiting intestinal microbial TMA lyase activity (119). Thus, DF intervention for individuals with various clinical statuses is expected to become an emerging treatment against CRC.…”
Section: Diet Modulationmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistent with this, a recent study investigated concentrations of fecal and serum BAs in vegans and omnivores, showing a vegan diet low in fat and high in fiber was positively correlated with fecal BA concentrations (118). Additionally, Li et al have suggested that supplying the DF diet to mice can reduce TMA and TMAO outputs via inhibiting intestinal microbial TMA lyase activity (119). Thus, DF intervention for individuals with various clinical statuses is expected to become an emerging treatment against CRC.…”
Section: Diet Modulationmentioning
confidence: 79%
“…Additionally, Li et al. have suggested that supplying the DF diet to mice can reduce TMA and TMAO outputs via inhibiting intestinal microbial TMA lyase activity ( 119 ). Thus, DF intervention for individuals with various clinical statuses is expected to become an emerging treatment against CRC.…”
Section: Diet Modulationmentioning
confidence: 99%
“…The superpathway “methylglyoxal degradation IV” has a low coverage in subjects MH0001 and MH0004 ( Figure 6 ). Methylglyoxal is a product of glucose and glycine metabolism that increases the activity of the gut microbial trimethylamine (TMA)-lyase [ 46 ]. TMA lyase catalyzes the transformation of dietary choline and carnitine to TMA, which in turn is metabolized by the liver to trimethylamine-N-oxide (TMAO), a potential risk factor for cardiovascular diseases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that bacteria of the genera Bacillus and Cellulomonas are included in probiotic preparations for animals, which exert anti-inflammatory effects on the intestinal barrier ( 51 , 52 ). Moreover, a previous study reported that Bacillus in the cecal digesta of mice was positively associated with TMA lyase activity ( 53 ). It is well established that TMA lyase plays a key role in converting choline to TMA and then it is oxidized to TMAO; thus, the increased abundance of Bacillus is in line with the higher plasma TMAO concentration in the current study.…”
Section: Discussionmentioning
confidence: 99%